Defect layer method to capture effect of gaps and overlaps in variable stiffness laminates made by Automated Fiber Placement - Fayazbakhsh, Kazem; Arian Nik, Mahdi; Pasini, Damiano; Lessard, Larry (Composite structures, 2013)
A variable stiffness design can increase the structural performance of composite laminates. In this paper, a composite laminate with curvilinear fiber paths is designed to maximize simultaneously its in-plane stiffness and buckling load. After obtaining the Pareto front through a surrogate-based optimization algorithm, two variable stiffness laminates among the solution set are selected that can be manufactured by an Automated Fiber Placement machine. Due to the characteristics of the manufacturing process, defects appearing in the form of gaps and/or overlaps emerge within the composite laminate. MATLAB subroutines are developed here to capture the location and extent of the defects. A novel method, called defect layer, is proposed to characterize the change in properties of each layer in the composite laminates that results from the occurrence of gaps and overlaps. Such a method allows calculating the in-plane stiffness and buckling load of a composite laminate with embedded defects. The results show that by incorporating gaps in the laminates the buckling load improvement resulting from fiber steering reduces by 15% compared to the laminates where gaps are ignored. A maximum improvement of 71% in the buckling load over the quasi-isotropic laminates can be observed for a variable stiffness laminate built with a complete overlap strategy.